Ada Lovelace: A Simple Solution to a Lengthy Controversy - Charman-Anderson, Suw (Patterns (N Y), 2020)
Ada Lovelace’s mathematical abilities have been widely questioned due to a misdating of her correspondence with Augustus de Morgan. Despite its correction in the academic record, this error persists in popular depictions of her work, undermining Lovelace herself and women in general. More scholarly examinations of historical women in STEM would enrich our understanding of their contributions and bolster their positions as role models.